Prevalence and prognostic value of right ventricular dysfunction in hypertrophic cardiomyopathy. (25th November 2020) - Marques, A; Pereira, A.R; Cruz, I; Almeida, A.R; Alegria, S; Briosa, A; Grade Santos, J; Sebaiti, D; Lopes, L; Joao, I; Pereira, H
Abstract: Introduction: Hypertrophic cardiomyopathy (HCM) is the main cause of sudden cardiac death in the young and a cause of heart failure and death at any age. Nevertheless, adverse long-term outcomes are not easy to predict. Objectives: To assess the prevalence, predictors and prognostic value of right ventricular (RV) dysfunction in patients (pts) with HCM. Methods: Retrospective single-center study of consecutive pts with HCM evaluated in a specialized medical appointment. Selected those submitted to cardiac magnetic resonance imaging (MRI) as the gold-standard for RV function assessment. The primary endpoint was a composite of cardiovascular death, nonfatal myocardial infarction, nonfatal stroke, ventricular arrhythmias with hemodynamic instability and unplanned heart failure admission. Results: Were included 112 pts (mean age at first appointment 57±15 years, 63% male). Septal asymmetric phenotype was the most frequent (75%), with a mean septal wall thickness of 18±4 mm. Late gadolinium enhancement was observed in 82%, mostly intramyocardial (67%) and in joint points (47%). RV dysfunction was detected in 6 pts (5.4%) and RV free wall hypertrophy in 3 pts (2.7%); no patient presented RV dilation. Factors associated with RV dysfunction were left atria area (HR 1.07/unit, 95% CI 1.01–1.12, p=0.02), left ventricular ejection fraction (HR 0.91/unit, 95% CI 0.86–0.97, p=0.02) and the presence of left ventricle wall motion abnormalities (HR 7, 95% CI 1.3–38, p=0.03) in cardiac MRI. During a mean follow-up of 60±31 months, the combined primary endpoint occurred in 15 pts (13%), significantly more in pts with RV dysfunction (HR 5.1, 95% CI 1.1–24, p=0.038) (graphic 1). Patients with RV dysfunction also presented more atrial fibrillation / flutter episodes during follow-up (HR 6.4, 95% CI 2.1–20, p=0.001). Conclusions: Although not common, right ventricular dysfunction was associated with a higher rate of cardiovascular events. These results support a potential role of right ventricular function in the risk stratification of patients with hypertrophic cardiomyopathy. Funding Acknowledgement: Type of funding source: None